Skp2 inhibits FOXO1 in tumor suppression through ubiquitin-mediated degradation - Huang, Haojie (National Academy of Sciences, 2005)
Forkhead transcription factors FOXO1 (FKHR), FOXO3a (FKHRL1), and FOXO4 (AFX) play a pivotal role in tumor suppression by inducing growth arrest and apoptosis. Loss of function of these factors due to phosphorylation and proteasomal degradation has been implicated in cell transformation and malignancy. However, the ubiquitin ligase necessary for the ubiquitination of the FOXO factors and the relevance of this regulation to tumorigenesis have not been characterized. Here we demonstrate that Skp2, an oncogenic subunit of the Skp1/Cul1/F-box protein ubiquitin complex, interacts with, ubiquitinates, and promotes the degradation of FOXO1. This effect of Skp2 requires Akt-specific phosphorylation of FOXO1 at Ser-256. Moreover, expression of Skp2 inhibits transactivation of FOXO1 and abolishes the inhibitory effect of FOXO1 on cell proliferation and survival. Furthermore, expression of the FOXO1 protein is lost in a mouse lymphoma model, where Skp2 is overexpressed. These data suggest that the Skp2-promoted proteolysis of FOXO1 plays a key role in tumorigenesis.